不同储油温度对芝麻油品质保鲜效果的影响"Effect of different storage temperature on the quality preservation of sesame seed oil" - 黄会娜1，王慧云2，史海明2，张梅3，姜元荣2，徐拥军3，易智伟1，刘玉兰4，马宇翔4" HUANG Huina1, WANG Huiyun2, SHI Haiming2, ZHANG Mei3, JIANG Yuanrong2, XU Yongjun3, YI Zhiwei1, LIU Yulan4, MA Yuxiang4" (Zhongguo youzhi)
旨在为芝麻油低温储存技术提供参考，分别对小磨芝麻香油、机榨芝麻香油和精炼芝麻油进行低温（15 ℃）、常温（25 ℃）、高温（45 ℃）条件的储存试验，定期取油样对其酸值、过氧化值以及维生素E、甾醇、芝麻木酚素含量进行检测，分析不同储油温度对3种芝麻油品质保鲜效果的影响。结果表明：经196 d储存，45 ℃下3种芝麻油的过氧化值升高至0.41~1.80 mmol/kg，酸值（KOH）升高至0.32~2.23 mg/g，15 ℃较45 ℃储存时3种芝麻油的过氧化值降低51.7%~75.6%，酸值降低36.9%~56.3%，3种芝麻油的过氧化值、酸值均未超出国标限量；15 ℃储存条件下3种芝麻油中维生素E损失6.7%~15.8%，甾醇损失18.5%~29.8%，45 ℃储存条件下3种芝麻油中维生素E损失20.8%~23.0%，甾醇损失21.2%~31.2%；芝麻木酚素含量在不同温度储存期间基本无变化。综上，15 ℃低温储油对抑制和减缓芝麻油过氧化值、酸值升高，以及减少维生素E、甾醇损失均具有明显效果，因而低温储油是值得推广应用的绿色储油技术。 To provide reference for the low-temperature storage of sesame seed oil, the storage tests of sesame seed oil (aqueous extracted fragrant sesame seed oil, pressed fragrant sesame seed oil, and refined sesame seed oil) were conducted at low temperature (15 ℃), room temperature (25 ℃), and high temperature (45 ℃), and the acid value, peroxide value, and the contents of vitamin E, sterol, and sesame lignan in the sesame seed oil during storage were determined to analyze the effects of different storage temperatures on their quality preservation. The results showed that after 196 d of storage, the peroxide values of the three kinds of sesame seed oils stored at 45 ℃ increased to 0.41-1.80 mmol/kg, and the acid values increased to 0.32-2.23 mgKOH/g. The peroxide values and acid values of the three kinds of sesame seed oils stored at 15 ℃ were reduced by 51.7%-75.6% and 36.9%-56.3%, respectively, compared with those stored at 45 ℃, and the peroxide values and acid values of the three kinds of sesame seed oils did not exceed the national standard limit. The loss of vitamin E in three kinds of sesame oils stored at 15 ℃ was 6.7%-15.8%, compared to 208%-23.0% at 45 ℃. Sterol loss at 15 ℃ was 18.5%-29.8%, compared to 21.2%-31.2% at 45 ℃. The sesame lignan content in sesame seed oil had no change during storage at different temperatures. In summary, the storage of oil at 15 ℃ has obvious effects on inhibiting the increase of peroxide value and acid value of sesame seed oil and reducing the loss of vitamin E and sterol, and low-temperature storage can be used as an environmentally friendly approach to preserve sesame seed oil quality.